Juridical construction of proving state losses in SOE corruption crimes after the distinction of corporate losses and state losses - N Indrajaya; Yasmirah Mandasar Saragih; Tuti Widyaningrum; Daniel Ricky Junianto; Cipto Hardoyo (Institute Of computer Science (IOCS), 2026)
This article analyzes the legal implications of the separation between corporate losses and state losses in the governance of State-Owned Enterprises (SOEs) following the enactment of Law Number 1 of 2025 on SOEs. Historically, losses incurred by SOEs have been automatically construed as state financial losses, leading to the extensive application of criminal law to business decisions and generating legal uncertainty for SOE management. This study aims to examine the genealogy of the concept of state loss, the transformation of the legal paradigm introduced by the 2025 SOE Law, and the juridical consequences of distinguishing corporate losses from state losses within the framework of public accountability. This research employs a normative juridical approach, supported by statutory, conceptual, and case analysis, particularly Constitutional Court decisions related to state finance and SOEs. The findings show that the 2025 SOE Law marks a significant shift toward a corporate law paradigm by affirming the principle of separate legal entity and limiting the automatic qualification of SOE losses as state losses. However, the study also finds that this separation cannot be applied in a purely formal manner. Corporate losses may still constitute state losses when arising from abuse of authority, unlawful acts, or actions that cause substantial harm to state finances or the national economy. The article concludes that a functional and impact-based approach is essential to balance corporate autonomy with public accountability. Clear juridical criteria and regulatory harmonization are necessary to prevent both the criminalization of legitimate business risks and the erosion of accountability in SOE governance.